What Makes a Stock Risky? Evidence from Sell‐Side Analysts' Risk Ratings - LUI, DAPHNE; MARKOV, STANIMIR; TAMAYO, ANE (Journal of Accounting Research, 2007)
ABSTRACT We examine the determinants and the informativeness of financial analysts' risk ratings using a large sample of research reports issued by Salomon Smith Barney, now Citigroup, over the period 1997–2003. We find that the cross‐sectional variation in risk ratings is largely explained by variables commonly viewed as measures of risk, such as idiosyncratic risk, size, book‐to‐market, and leverage. In addition, earnings‐based measures of risk, such as earnings quality and accounting losses, also contribute to explaining the cross‐sectional variation in the risk ratings. Finally, we document that the risk ratings can be used to predict future return volatility after controlling for other predictors of future volatility. We conclude that analysts play an important role as providers of information about investment risk.